1997
DOI: 10.1097/00000658-199712000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preoperative Transarterial Lipiodol Chemoembolization on Resection and Transplantation for Hepatocellular Carcinoma in Patients With Cirrhosis

Abstract: ObjectiveTo investigate the impact of preoperative transarterial lipiodol chemoembolization (TACE) in the management of patients undergoing liver resection or liver transplantation for hepatocellular carcinoma. Patients and MethodsTACE was performed before surgery in 49 of 76 patients undergoing resection and in 54 of 111 patients undergoing liver transplantation. Results were retrospectively analyzed with regard to the response to treatment, the type of procedure performed, the incidence of complications, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
371
1
10

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 479 publications
(397 citation statements)
references
References 48 publications
(7 reference statements)
13
371
1
10
Order By: Relevance
“…Most of the published reports have used the Milan criteria as the endpoint of down-staging. [3][4][5][6][7][8] The Response Evaluation Criteria in Solid Tumors (RECIST) [9][10][11] and other criteria 12,13 have also been used to define the response to tumor down-staging, especially when eligibility for LT is not restricted to patients meeting the Milan criteria. Because we are defining the response to down-staging according to measurements of only the viable tumor after locoregional therapy, the RECIST approach does not fit well into this scheme: it defines treatment responses according to the measurement of the entire tumor (including both the ablated or necrotic portion and the viable tumor).…”
Section: What Should Be the Endpoint Or Endpoints Of Down-staging?mentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the published reports have used the Milan criteria as the endpoint of down-staging. [3][4][5][6][7][8] The Response Evaluation Criteria in Solid Tumors (RECIST) [9][10][11] and other criteria 12,13 have also been used to define the response to tumor down-staging, especially when eligibility for LT is not restricted to patients meeting the Milan criteria. Because we are defining the response to down-staging according to measurements of only the viable tumor after locoregional therapy, the RECIST approach does not fit well into this scheme: it defines treatment responses according to the measurement of the entire tumor (including both the ablated or necrotic portion and the viable tumor).…”
Section: What Should Be the Endpoint Or Endpoints Of Down-staging?mentioning
confidence: 99%
“…14 Published data on the outcomes of tumor downstaging for LT are summarized in Tables 1 and 2; the data are classified according to the endpoint of downstaging. The concept of applying locoregional therapy to reduce the size of HCC tumors and thus facilitate resection or LT was first tested by Majno et al 13 (Hôpital Paul-Brousse, Villejuif, France). Two subsequent studies have suggested that a response to locoregional therapy with transarterial chemoembolization (TACE) for HCC meeting or exceeding the Milan criteria could serve as a prognostic marker for improved posttransplant outcomes and for the selection of LT candidates.…”
Section: What Should Be the Endpoint Or Endpoints Of Down-staging?mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been performed by several transplantation centers. [3][4][5][6] The new aspect in our approach is that patients exceeding the Milan criteria 7 were downstaged, 8 and, in contrast to any other study, the patients listed for LT were continuously treated by TACE during the waiting period according to a strict protocol. Risk of tumor recurrence was low in the patients without measurable tumor progress compared with patients with minimal tumor progress during the waiting time, even if this "progress" remained within the official definition of stable disease.…”
mentioning
confidence: 99%